KUALITAS PELAYANAN TRANSJAKARTA DALAM MEMENUHI KEBUTUHAN TRANSPORTASI UMUM DI JAKARTA SELATAN - Angelina Amanda; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Transjakarta, as a public transportation system in Jakarta, plays a strategic role in reducing traffic congestion and meeting the mobility needs of the community. However, in its implementation, several problems are still encountered, particularly in South Jakarta on Corridors 13 and 6, such as an imbalance between fleet capacity and passenger demand as well as suboptimal service performance. This study aims to analyze the service quality of Transjakarta in meeting public transportation needs and to identify the supporting and inhibiting factors affecting service delivery. The research employs a descriptive qualitative approach using data collection techniques including observation, interviews, documentation, and questionnaires distributed to service users. The results indicate that the service quality of Transjakarta in South Jakarta is categorized as fairly good, as reflected in seven service dimensions: Self Esteem, Exceed Expectation, Recovery, Vision, Improve, Care, and Empower. The service is supported by staff professionalism, continuous training programs, facility improvements, and intermodal integration. Nevertheless, limitations in fleet availability, passenger overcrowding, facility disruptions, and inadequate stop accessibility remain significant challenges. Therefore, continuous improvement efforts are required to enhance the overall quality of Transjakarta services optimally.